2020
DOI: 10.1109/access.2020.2965259
|View full text |Cite
|
Sign up to set email alerts
|

A Model-Driven Mobile HMI Framework (MMHF) for Industrial Control Systems

Abstract: With the advent of software technologies, over a period of time, the Industrial Control Systems (ICSs) have grown exponentially. Whereas, almost all ICSs comprise Human Machine Interfaces (HMIs), which are the key component for monitoring and controlling complex industrial systems. For decades, traditional HMIs with simple User Interfaces (UIs) remained operational to minimize the complexities and resulting operational costs. However, due to the emergence of smartphone technologies, the perception about user i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Most information systems involve human-computer interaction (HCI). Therefore, HCI has become a key component of any complex system [169], and has become one of the key parts of intelligent manufacturing management [170,171]. According to the vertical framework of the MC-SIOT system, the managers can make real-time decisions through HCI at the management level.…”
Section: Human-computer Interactionmentioning
confidence: 99%
“…Most information systems involve human-computer interaction (HCI). Therefore, HCI has become a key component of any complex system [169], and has become one of the key parts of intelligent manufacturing management [170,171]. According to the vertical framework of the MC-SIOT system, the managers can make real-time decisions through HCI at the management level.…”
Section: Human-computer Interactionmentioning
confidence: 99%
“…We practice a Model-to-Text (M2T) transformation approach, using the open source Acceleo tool [16], for the implementation of MODEVES Transformation Engine (MTE). Acceleo is a well-known tool for a seamless execution of transformations in MBSE [29]. Figure 5 shows that the implementation of MTE is accomplished through three main modules: (1) User Interface, (2) Generator and (3) Java Services.…”
Section: A General Architecturementioning
confidence: 99%
“…The validation of MAF is performed in our institution's control lab. An open source Modbus-based Data Acquisition (DA) server is used for the validation of MAF [12]. To develop realistic environment, two Fatek PLCs [38] are utilized where 300 tags are configured to fetch real time values from DA server in order to process alarms accordingly.…”
Section: A Experimental Setupmentioning
confidence: 99%
“…They can acquire, process and log real-time data for particular industrial process. Furthermore, they allow direct and instant monitoring of industrial processes through Human Machine Interface (HMI) [12]. The basic architecture of industrial control systems is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation